Interdisciplinary Approaches to Understanding and Managing the Interrelationship Between Pediatric Obesity and Functional Gastrointestinal Disorders: A Comprehensive Review - Alotaibi, Mohammed Matar; ALHARTHI, MUHANNAD ABDULKARIM; Bahsan, Ahmed Essa Mousa; Alotaibi, Mohammed marzoq; Alotaibi, Saad Refaie; aldalbahi, Bandar mashal; lutfallah , Fatima saeed; AlGhamdi, Mosleh Motesh Saud; Alotibi, mejhez saud; TWAIM, SATTAM NASSIR BIN; Alghbaywi, Abdulrahman khalid Ghayib; Alotaibi , Refah daifullah; et al. (Journal of Ecohumanism, 2024)
Background: Functional gastrointestinal disorders (FGIDs) are prevalent among children and adolescents, often linked to obesity and associated digestive issues. Understanding the interplay between obesity and FGIDs is critical for developing effective management strategies. Methods: This narrative review examines the correlation between obesity and functional bowel disorders (FBDs) in pediatric populations. A thorough literature search was conducted on the PubMed database, focusing on English-language studies published in recent years. The review highlights the epidemiology, pathophysiology, and management approaches for FGIDs in the context of pediatric obesity. Results: The findings indicate a significant association between obesity and FGIDs, with studies reporting higher prevalence rates of conditions such as Irritable Bowel Syndrome (IBS) and Functional Constipation (FC) in overweight children. The review identifies several common risk factors, including dietary habits, gut microbiota alterations, and psychological distress. Interventions, such as dietary modifications and nutritional education, have shown promise in alleviating symptoms and improving health outcomes. However, variability in research methodologies and outcomes necessitates further investigation. Conclusion: The management of obesity-related FGIDs in pediatric patients requires a multidisciplinary approach that incorporates dietary strategies, psychological support, and lifestyle modifications. Future research should focus on elucidating the mechanisms linking obesity and FGIDs and developing targeted interventions tailored to individual patient needs. Addressing these comorbid conditions holistically can enhance the quality of life for affected children and adolescents.